T cell receptor diversity and activation markers in the V delta 1 subset of rheumatoid synovial fluid and peripheral blood T lymphocytes. - Bucht, A; Söderström, K; Hultman, T; Uhlén, M; Nilsson, E; Kiessling, R; Grönberg, A (1992)
In the present study we have characterized the gamma/delta T cell receptor (TcR) population in synovial fluid (SF) and peripheral blood (PB) of patients with chronic inflammatory arthritis. By double staining we have shown that (a) synovial V delta 1+ cells have a high expression of activation markers CD45R0 ("memory cells") and HLA-DR as compared to PB, indicating a preactivated population of V delta 1-carrying T cells in vivo and (b) interleukin 2-induced expansion of synovial cells yields a high proportion of gamma/delta in most samples expressing predominantly the V delta 1 TcR. Junctional sequence analysis of the TcR delta chain from interleukin 2-expanded PB cell lines demonstrated a polyclonal V delta 1 population in three out of three samples. In SF cell lines three out of four samples were polyclonally expanded. In SF from one patient, however, a limited repertoire of expressed V delta 1 genes was found. Altogether, our data demonstrate the presence of preactivated V delta 1-expressing cells in the synovial compartment. This V delta 1 population is predominantly polyclonal, except in one patient where oligoclonally expanded V delta 1 cells were detected.